Does the BRRD affect the retail banking business model in the Euro area?. (11th February 2020) - Tropeano, Domenica
Abstract: This paper discusses how the introduction of the Banking Recovery and Resolution Directive (BRRD) in European Union legislation may change the retail banking business model, which is the most prevalent model in Southern European countries. The main point is the treatment of deposits in the BRRD. Uninsured deposits may be written down or converted into equity in case of resolution of a bank. This contrasts with the treatment of other short‐term liabilities, in particular repurchase agreements. Short maturity repos are excluded from the bail‐in, regardless of their size. Also, liabilities related to securities lending and derivatives are given privileged treatment. It is argued that this will be an advantage for wholesale and investment banks, which use these types of short‐term funding largely to finance asset purchases. Moreover, it will severely hit retail banking business models of various types by undermining the trust of depositors in the bank, causing bank runs whenever rumours circulate about financial distress situations, thus increasing its cost of funding and lowering the value of its shares. Therefore, to avoid runs on repos, runs on banks are resurging.